Solar UAV : aerodynamic configuration of solar UAV and wind tunnel model studies - Chan, Yi Cheng. (2013)
The Solar Unmanned Aerial Vehicle (UAV) project was instigated by Defence Science Organisation (DSO) National Laboratories, Singapore, in 2011, to develop a perpetual flying platform for surveillance and other missions. In this 2nd year of the 3-year assignment, Final Year undergraduates will look into improving the efficiencies of UAV system established in the 1st year, as well as fabricate parts of the full scaled prototype Solar UAV. The purpose of this Final Year Project (FYP) is to present the configuration design of the Solar UAV platform and fabricate the required scaled-down model for wind tunnel tests.